Intrauterine infusion of platelet‐rich plasma is a treatment method for patients with intrauterine adhesions after hysteroscopy - Peng, Jintao (Int J Gynaecol Obstet, 2020)
OBJECTIVE: To evaluate the efficacy of an intrauterine infusion of platelet‐rich plasma (PRP) in patients with intrauterine adhesions (IUAs). METHODS: A retrospective study was conducted from April 2018 to December 2019 to compare the efficacy of intrauterine infusion of PRP with balloon for patients with IUAs. All patients had moderate or severe IUAs, including 28 patients with intrauterine infusion of PRP (group A), 22 patients with intrauterine balloon (group B), and 20 patients with both intrauterine infusion of PRP and balloon in the first operative hysteroscopy. American Fertility Society (AFS) score and rates of chemical pregnancy were compared. RESULTS: The AFS score decreased with an average of 5.18 ± 3.93, 4.91 ± 4.39, and 5.15 ± 3.17 comparing the third hysteroscopy with the first operative hysteroscopy in group A, group B, and group C, respectively. No significant differences were found among these groups (P=0.734). The rates of chemical pregnancy were 40.0% in group A, 38.9% in group B, and 33.3% in group C without significant differences (P=0.944). CONCLUSION: There were no significant differences between intrauterine infusion of PRP and balloon. PRP is a treatment method for IUAs.